KONSEP SHAUM SEBAGAI MEDIA TAZKIYATUN NAFS DALAM TAFSIR FAID AR-RAHMAN KARYA KH. SHOLEH DARAT - Muhammad Fadhil Wathani; Faizun Faizun; Sukendar Sukendar (Adisam Publisher, 2025)
This study examines the concept of fasting as a medium of tazkiyatun nafs (purification of the soul) from the perspective of KH. Sholeh Darat through Tafsir Faidh al-Rahman. KH. Sholeh Darat, a 19th-century scholar of the archipelago, interpreted fasting through a Sufi approach that emphasized the spiritual and inner dimensions. In Al-Baqarah verse 183, he divides fasting into three levels: physical fasting (shari'ah), fasting of the limbs (thariqah), and fasting of the heart (haqiqah), in line with Al-Ghazali's thought. Fasting is not only aimed at individual piety but also has a social impact, such as increasing self-awareness, brotherhood, and community order. This study demonstrates that a holistic understanding of fasting, combining aspects of fiqh and Sufism, is relevant for overcoming the limited knowledge of those who focus solely on legal aspects. Fasting is regarded as an effective means of spiritual transformation, purifying the soul and leading to a more meaningful life.